قياس مستوى مهارة الكلام باللُّغة العربيَّة لدى طلبة تحفيظ القرآن الكريم:دراسة حالة على معاهد التَّحفيظ التَّكامليَّة والعلوم والتُّكنولوجيا بولاية سلانجور في ماليزيا - Alosman, Abdulrahman; Othman, Asem; Mohamad Kamal, Nurul Afiqah; Abdul Hamid, Mohd Fauzi (SIBAWAYH Arabic Language and Education, 2025)
الملخص يتساءل الباحثون عن مدى استطاعة حَفَظَةِ القرآن الكريم من متعلِّمي اللغة العربية الكلامَ باللغة العربيَّة؛ نظرًا لثراء حصيلتهم اللغوية من الكلمات القرآنية الواردة في سياق حفظهم الغيبي، إذ ينبغي أن تكون درجة مستواهم في مهارة الكلام عالية، خاصَّة وأنَّهم يعالجون حفظ الكلمات ومراجعتها مرارًا كل يوم. هدفت الدِّراسة الحالية إلى قياس مستوى طلبة تحفيظ القرآن الكريم في الكلام باللُّغة العربيَّة، والكشف عن الفروق ذات الدلالة الإحصائية بين الطلبة الذكور والإناث في المعاهد المذكورة. انتهج الباحثون في تحقيق هذين الهدفَيْن بالاستعانة بمنهج دراسة الحالة بالمدخل الكمِّي من خلال البيانات الواردة من إجراء اختبار تحديد مستوى مهارة الكلام للطلبة، وتحليلها باستخدام برنامج تحليل الرُّزَم الإحصائيَّة (SPSS) للوصول إلى النتائج التي أشارت إلى أنَّ أفراد عيِّنة الدِّراسة من كلا المعهدَين (كلانغ وجغرا) يتمتَّعون عموماً بمستوى مقبول إلى جيِّد في مهارة الكلام باللغة العربية، مع تفوُّقٍ عدديٍّ بسيط للإناث، وتفوُّقٍ طفيف في النِّسب المئويَّة والمتوسِّطات الحسابيَّة لصالح طلبة معهد كلانغ مقارنةً بمعهد جغرا، كما ظهرت بعض الفروق الوصفيَّة بين الذُّكور والإناث، ولا سيما انخفاض أداء إناث معهد جغرا مقارنةً ببقيَّة المجموعات، غير أنَّ هذه الفروق ظلَّت محدودة وغير حاسمة إحصائيًّا؛ إذ أظهرت نتائج اختبار-ت عن عدم وجود فروق ذات دلالة إحصائيَّة بين متوسِّطات درجات الذُّكور والإناث في مهارة الكلام، ممَّا يدلُّ على أنَّ الاختلافات الملحوظة تعود في الغالب إلى التفاوت الفردي داخل المجموعات أكثر من ارتباطها بالجنس أو بنوع الفصل الدِّراسي، ويؤكِّد ذلك أنَّ أداء الطلبة في المعهدين يقع ضمن مستويات النجاح، مع قلَّة حالات الرسوب ووجود حالات تفوُّق مرتفع، دون أن يصل هذا التباين إلى مستوى الدلالة الإحصائيَّة. الكلمات المفتاحية: قياس؛ مستوى؛ مهارة الكلام؛ طلبة تحفيظ القرآن؛ معاهد التحفيظ التكاملية والعلوم والتكنولوجيا بولاية سلانجور Abstract Researchers often question the extent to which Qur’an memorizers who are learning Arabic are able to speak the language, given the richness of their linguistic repertoire derived from the Qur’anic vocabulary they encounter through intensive memorization. Their level of speaking skill is expected to be high, especially since they process and review these words repeatedly every day. The present study aimed to measure the Arabic-speaking proficiency of students in Qur’an memorization programs and to identify statistically significant differences between male and female students in the selected institutes. The researcher pursued these two objectives using a quantitative case study approach based on data obtained from a test to determine the students’ speech skills, which was analyzed using the Statistical Package for the Social Sciences (SPSS) program. (SPSS) to arrive at results indicating that the study sample from both institutes (Klang and Jaga) generally had an acceptable to good level of Arabic speaking skills, with a slight numerical superiority for females and a slight advantage in percentages and arithmetic means in favor of Klang Institute students compared to Jagra Institute students. There were also some descriptive differences between males and females, particularly the lower performance of females at the Jaga Institute compared to the rest of the groups, but these differences remained limited and statistically insignificant. The results of the t-test showed that there were no statistically significant differences between the average scores of males and females in speaking skills, indicating that the observed differences were mostly due to individual variation within the groups rather than gender or class type. This confirms that the performance of students at both institutes is within the range of success, with few cases of failure and many cases of high achievement, without this variation reaching a statistically significant level. Keywords: Measuring, Proficiency Level, Speaking Skill, Qur’an Memorization Students, Integrated Tahfiz Institutes of Science and Technology in Selangor (MITS)